Karakter Kaum Yahudi dalam Al-Qur’an dan Relevansinya terhadap Agresi Zionis dalam Tragedi Thufan al-Aqsha: Kajian Tafsir Tematik - Marina, Silvia; Hably, Roby; Tamsin, Fadil Menggala Putra; Mubarok, Alfian (Faculty of Tarbiyah and Teacher Training, 2025)
The Qur’an frequently refers to the Jews in various contexts, ranging from the story of Prophet Moses to stern warnings directed at Muslims not to imitate their behavior. In numerous verses, they are described as “those who incurred [God’s] wrath” due to their corrupt morals and deviant actions, such as altering divine revelation, breaking covenants, and considering themselves as God’s chosen people. Their negative traits are recorded in several chapters of the Qur’an, including Al-Mā’idah: 20–22, Al-Baqarah: 146, Al-Fātiḥah: 6, and Al-Mā’idah: 24. According to the Qur’an, this arrogant attitude is not merely a historical fault but closely resembles the ideological patterns and actions of modern Zionists, particularly evident in the tragedy of Thufān al-Aqṣā. This event demonstrated how violence and occupation carried out in the name of Zionist ideology reflect the same characteristics that the Qur’an has long criticized. hrough a thematic exegesis approach and a historical-political analysis, it becomes evident that Zionist aggression toward Palestine is not merely a territorial political issue, but rooted in a deeper spiritual and ideological character condemned by the Qur’an. The method used in this research is library research with a thematic exegesis (tafsīr mawḍūʿī) approach, which involves a comprehensive study of Qur’anic verses that address the characteristics of the Jews, analyzed through the interpretations of both classical and contemporary scholars.